Perfil volátil do queijo de coalho artesanal e industrializado durante vida de prateleira - Santos, Geovane do (2018)
Traditional from the northeastern region of Brazil, “coalho” cheese is widely produced and consumed in the states of Pernambuco, Ceará, Paraíba and Rio Grande do Norte. denominated in this way because was traditionally produced with stomach piece of animals (mocó, preá, goatling and calf), which properly prepared served as rennet. Presents in its sensorial characteristics: semi-hard and elastic consistency; compact and soft texture; yellowish white color; slightly acid odor that remember coagulated mass; thin crust without crack; its not common the bark formation; with absence or presence of small holes. The aroma, more known as smell, is one of the main sensory attributes related to food acceptability. Despite of “coalho”cheese be produced over 150 years in the northeastern region of Brazil, there is not many studies about its volatile profile. Then, the present work had the purpose to study the volatile profile of “coalho” cheese, craft and industrial, during ten ripening days (1; 5 and 10). Ten samples of “coalho” cheese were used, of which five of craft “coalho” cheese and the others of industrial “coalho” cheese. Volatile compounds were extracted using SPME (Solid Phase Micro Extraction) technique and analyzed by gas chromatography coupled to mass spectrometry. 36 volatile compounds were found in craft “coalho” cheese: 7 alcohols, 8 ketones, 9 esters, 6 acids, 2 aldehydes, 3 terpenes and 1 hydrocarbons. In the industrial “coalho” cheese, 32 volatile compounds were identified: 14 alcohols, 7 acids, 6 ketones, 3 aldehydes, 1 ester and 1 terpene. Among the compounds identified, the most relevant were hexanoic acids (OAV 63,32), phenyl acetate (OAV 22,14), butanoic acid (OAV 16,96), nonanal (OAV 15,12) and ethyl octanoate (OAV 9,5).During the maturation period, esters and ketones had an increase in their OAVs for artisanal cheeses, increasing their contribution positively with a pleasant aroma minimizing the effect of unwanted aroma compounds such as hexanoic acid. For industrialized cheeses only 2-nonanone increased considerably during the maturation period, which may lead to a greater perception by the consumer of the unwanted aroma at the end of the maturation period, since there was a considerable increase in the contribution of hexanoic acid, characterized with aromatic notes of "sweat", "fat" and "sour."